2002
DOI: 10.2134/agronj2002.7980
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Response to Nitrogen at Multiple In‐Field Locations

Abstract: Improving N management for corn (Zea mays L.) production with precision agriculture technologies requires that spatial N recommendations adequately represent in‐field variability in N availability. Our objective was to evaluate corn response to increasing N rates in several in‐field locations that represented the range of soil organic matter (OM) content in the field. In a 2‐yr study, three center pivot–irrigated fields were selected in south‐central Kansas and south‐central Nebraska. Four or five locations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 26 publications
4
46
2
Order By: Relevance
“…At Australia, from large scale demonstration it has been reported that recovery efficiency was 37% for broadcasting and 49% for deep placement of USG in rice; hence deep placement of N fertilizers can improve nitrogen recovery (Balasubramanian et al, 2002). Placement of urea with mud balls technique in the reduced zone of transplanted puddled rice field also improves N recovery and gave better crop output (Schmidt et al, 2002). Further, foliar feeding of nitrogen either through urea spray, can also improve NUE as it reduce different losses i.e.…”
Section: Improved Methods Of N Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…At Australia, from large scale demonstration it has been reported that recovery efficiency was 37% for broadcasting and 49% for deep placement of USG in rice; hence deep placement of N fertilizers can improve nitrogen recovery (Balasubramanian et al, 2002). Placement of urea with mud balls technique in the reduced zone of transplanted puddled rice field also improves N recovery and gave better crop output (Schmidt et al, 2002). Further, foliar feeding of nitrogen either through urea spray, can also improve NUE as it reduce different losses i.e.…”
Section: Improved Methods Of N Applicationmentioning
confidence: 99%
“…Some genotypes may produce different grain yields with the same amount of N uptake. Differences in the efficiency of N acquisition may arise from (1) differences in the efficiency of absorption and assimilation of NH 4 + and other N species and their regulation (Schmidt et al, 2002); (2) the extent and distribution of roots, age of roots, and root induced changes in the rhizosphere affecting N mineralization, transformation, and transport ; and (3) root associated biological N fixation (Shrestha and Ladha 1996). While, differences in the efficiency of internal N use (PE N ) may arise from differences in (1) internal N requirements for growth, (2) ability to translocation, distribute and mobilize absorbed N to and from various organs, (3) flag leaf N import-export and leaf senescence patterns, and (4) the efficiency of converting CO 2 into carbohydrate .…”
Section: Enhancement Of N-use Efficiency Through Genetic Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical and nutrient profile of corn varies widely depending on factors such as cultivar and field location (Sproule et al 1988;Singh et al 2000;Schmidt et al 2002).…”
Section: Mots Clésmentioning
confidence: 99%
“…Although these sensing techniques have successfully identified N deficiencies, they do not effectively account for the spatially varying properties of the agricultural landscape or weather patterns that affect NO3-N losses from the agricultural system. Other researchers have attempted to develop yield response functions by regressing crop yield against soil nutrient measurements, such as late-spring NO3-N concentration (Katsvairo et al, 2003) and soil organic matter (Schmidt et al, 2002). High r 2 values for the relationship between crop yield and soil nutrient levels have not been consistently obtained with this approach, because the temporal aspects of N movement through the agricultural system cannot be adequately characterized by a single equation.…”
Section: Introductionmentioning
confidence: 99%